Career and Retirement Theories: Relevance for Older Workers Across Cultures. (June 2015) - Lytle, Megan C.; Foley, Pamela F.; Cotter, Elizabeth W.
This article reviews selected career development theories and theories specifically focused on retirement, with an emphasis on their application to retirement decisions and vocational behavior in multicultural populations. Theories are evaluated based on whether (a) retirement was considered a stage of working life, (b) work satisfaction, motivation, and other work variables at retirement age were addressed, (c) work choices at retirement age were included, and (d) cultural and other minority status issues were either directly considered in the work–retirement decision or if the model could be reasonably applied to retirement across cultures. We provide specific recommendations for research and practice with the aim of helping practitioners and scholars conceptualize the current concerns older adults face in their working lives and during retirement planning.